Analysis The Implementation Of Economic Order Quantity Method In Controlling The Inventory Of Raw Materials For Screen Printing T-Shirts At Raxgacloth Printing - Irvan, Mohammad; Fauji, Diah Ayu Septi (Proceeding Kilisuci International Conference on Economic & Business, 2024)
Research aim : This research aims to determine the optimal amount of raw materials for screen printed t-shirts at Raxgacloth Printing using the Economic Order Quantity (EOQ) method so as to minimize inventory costs such as ordering costs and storage costs. Design/Methode/Approach : This research uses a quantitative descriptive approach with data processing assisted by the POM QM application. The data used in this research is from December 2022 to November 2023. Research Finding : The research results show that controlling the inventory of t-shirt raw materials based on Raxgacloth Printing's policy resulted in 6,423 t-shirt units at a cost of Rp. 6,427,847 with an order frequency of 180 times a year. Meanwhile, by calculating raw material inventory using the Economic Order Quantity method, more optimal results were obtained, including purchasing raw materials for only 1,542 units of t-shirts at a cost of Rp. 380,425 and order frequency 4 times a year. For Safety Stock 36 units were obtained and Reorder Point was 74 units.